A conductive carbon coating anode for copper electroplating process and its preparation method and application

By using a conductive carbon coated anode with a titanium substrate in the electroplating copper plating process, the problems of waste, maintenance difficulties and high cost in the prior art are solved, and the electroplating effect with low cost, high conductivity and good uniformity is achieved.

CN118048603BActive Publication Date: 2025-03-14GUANGZHOU HUIKE HIGH-TECH MATERIALS TECH CO LTD

Patent Information

Application Number
CN202410120214.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-03-14
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

In the existing copper plating process, the phosphorus copper anode has problems such as waste, maintenance difficulties and insufficient uniformity, while the precious metal oxide coated titanium anode is expensive, which increases production and manufacturing costs.

Method used

A conductive carbon coating anode based on titanium is used, and a dense coating of high-purity carbon material is applied to the titanium substrate, and a high-conductivity and low-cost anode is formed by vacuum sputtering and thermal oxidation treatment.

Benefits of technology

The copper plating process with low cost, high conductivity and good uniformity is achieved, which reduces production costs and improves the uniformity of copper plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118048603B_ABST
    Figure CN118048603B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive carbon coating anode for copper electroplating process and its preparation method and application. The conductive carbon coating anode for copper electroplating process is based on a titanium plate, and a layer of conductive carbon coating is applied on the surface of the titanium plate by vacuum sputtering. The preparation method of the conductive carbon coating anode is to first roughen the titanium plate, and then use a high-purity carbon material as a target material to apply a dense conductive carbon coating on the titanium substrate in a vacuum by sputtering; then, the carbon coating titanium anode is energized under air-tight conditions to heat it to 1000-1500°C, energize it for 5-10 hours, and obtain a conductive carbon coating anode for copper electroplating process after cooling. The conductive carbon coating anode of the present invention is low in price, has better film thickness uniformity, and better conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electroplating, and in particular to a conductive carbon coating anode used in a copper electroplating process, and a preparation method and application thereof. Background Art

[0002] In the process of printed circuit board production, copper electroplating is one of the most important process links.

[0003] The copper plating device is mainly composed of a cathode, an anode and an electrolytic cell. There are two main types of anodes on the market: 1) Phosphor copper is used as the anode. This soluble anode is used as a supplement to copper ions. It is necessary to frequently drag the cylinder to maintain the anode film and activity, resulting in a large amount of phosphor copper anode waste. In addition, the phosphor copper anode will produce anode mud, which requires regular maintenance and cleaning, which wastes phosphor copper, produces a large amount of wastewater, and wastes manpower. More importantly, with the popularization of high-density fine circuits, the requirements for copper plating uniformity are getting higher and higher, and the phosphor copper anode can no longer meet the current requirements. 2) Insoluble anodes are used. This anode is mainly a precious metal oxide titanium anode. It is mainly to coat a precious metal such as iridium, tantalum and other one or more metal metal complex precursor solutions on the titanium substrate, and through the process of drying and thermal decomposition, a layer of catalytically active precious metal oxide coating is formed on the titanium surface. As we all know, the IrO2-Ta2O5 oxide-coated titanium anode commonly used in the circuit board copper plating process can solve the shortcomings of phosphor copper anodes, such as poor uniformity, such as the need for regular maintenance, etc. However, the price of iridium oxide, a precious metal in the insoluble anode coating, remains high. Currently, the market price of insoluble anodes is as high as RMB 30,000 per square meter. If an ordinary VCP line replaces the insoluble anode every two years, the cost of the insoluble anode for two years will reach more than RMB 2 million, which greatly increases the production and manufacturing costs of the client.

[0004] Therefore, a new anode material is needed. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is mainly to propose a conductive carbon coated anode for use in copper electroplating process. At the same time, the application also proposes a preparation method and application of the anode.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] The conductive carbon coating anode for copper electroplating of the present invention is based on titanium, and a conductive carbon coating is applied on the surface of the titanium substrate to replace the insoluble anode with precious metal iridium oxide and tantalum oxide as the coating. The advantages of this anode are: 1) simple manufacturing process; 2) low price; 3) better conductivity, further improving the uniformity of copper plating. The conductive carbon coating is made of materials selected from carbon black, graphite, carbon nanotubes, graphene, etc., with a purity of more than 99.9%.

[0008] The manufacturing process of the conductive carbon coating anode for copper electroplating process of the present invention is as follows:

[0009] 1) Roughening the titanium substrate, the roughening process is to put the titanium substrate into 8-12% hydrochloric acid solution, treat it at 60°C for 1 hour, wash it with water and dry it. Roughening the titanium substrate is beneficial to enhance the bonding force between the carbon coating and the substrate.

[0010] 2) Using high-purity carbon material as the target, a dense carbon coating is applied on the treated titanium substrate by sputtering in a vacuum. The carbon coating plated by vacuum sputtering has the characteristics of high hardness, high wear resistance (low friction coefficient), good corrosion resistance and chemical stability. The greater advantage is that the carbon coating has a high bonding force with the titanium substrate, good coating uniformity, and a longer film life.

[0011] 3) The carbon-coated titanium anode is energized under air-tight conditions to heat it to 1000-1500°C for 5-10 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained. The thermal oxidation treatment of the conductive carbon-coated anode is mainly to remove impurities and further enhance the bonding strength between the conductive carbon coating and the substrate, so that the coating and the substrate are firmly bonded together.

[0012] The anode can be widely used in various copper electroplating processes for circuit boards, such as DC through-hole electroplating, DC hole-filling electroplating, pulse electroplating, copper-dissolving system electroplating, etc.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1) Low price: The price of the conductive carbon in the present invention is about 100 yuan / kg, while the price of iridium oxide is about 500 yuan / gram, and the price difference is about 5000 times;

[0015] 2) Better film thickness uniformity: Currently, the preparation of iridium-tantalum anodes is still based on traditional coating processes, and is mainly manual operation, and the coating uniformity is poor. The carbon-coated anode obtained by vacuum sputtering has a more uniform film thickness and a more uniform distribution of electric lines, which helps to improve the problem of uniformity of copper electroplating.

[0016] 3) Better conductivity: Conductive carbon coating has better conductivity and lower voltage than precious metal oxide coating, which will further improve the uniformity of copper plating. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a diagram showing the effect of the conductive carbon coating anode of Example 1 of the present invention being used for hole-filling copper plating;

[0018] Figure 2 This is a diagram of the conductive carbon coating anode of Example 1 of the present invention being used for hole-filling copper plating in a copper-dissolving system;

[0019] Figure 3 This is a diagram showing the electroplating effect of the conductive carbon coating anode of Example 2 of the present invention being used for through-hole copper plating;

[0020] Figure 4 This is a diagram showing the electroplating effect of the conductive carbon coating anode of Example 2 of the present invention being used for pulse copper plating;

[0021] Figure 5 This is a hole-filling effect diagram of the conductive carbon coating anode of Comparative Example 1 of the present invention used for hole-filling copper plating;

[0022] Figure 6 This is a comparison chart of the tape stripping test of the conductive carbon coating anode of Comparative Example 2 of the present invention and the conductive carbon coating anode prepared in Example 2. DETAILED DESCRIPTION

[0023] In order to allow those skilled in the art to understand the present invention more clearly and intuitively, the present invention will be further described below in conjunction with the accompanying drawings.

[0024] Example 1

[0025] The preparation process of the conductive carbon coating anode of this embodiment is as follows:

[0026] 1) The titanium substrate is roughened. The roughening process includes placing the titanium substrate in a 8-12% hydrochloric acid solution, treating at 60° C. for 1 hour, washing with water and drying.

[0027] 2) Using high-purity graphite rod material as the target material, in a vacuum environment with a vacuum degree of 0.2 Pa, using 99.9% argon as the protective gas, controlling the vacuum coating temperature to 65°C, the coating time to 250 seconds, and the coating thickness to 4 microns, a dense graphite coating is applied on the treated titanium substrate by sputtering.

[0028] 3) The graphite-coated titanium anode is electrified in an airtight condition to heat it to 1000° C. for 5 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained.

[0029] The above conductive carbon coating anode is used in the hole filling copper plating process, according to the following electroplating solution configuration, the electroplating solution is stirred by air, the temperature is 25°C, the aperture of the blind hole on the test board is 125um, and the layer is 70um. Electroplating parameters: current density: 1.5ASD, electroplating time 50min.

[0030] Copper sulfate pentahydrate: 250g / L;

[0031] Sulfuric acid: 35g / L;

[0032] Chloride ion: 60mg / L;

[0033] Accelerator: 2mg / L;

[0034] Wetting agent: 0.8g / L;

[0035] Leveling agent: 0.5g / L.

[0036] The conductive carbon coating anode is used in the hole filling copper plating process. The hole filling effect obtained according to the above parameters is as follows: Figure 1 As shown, the surface of the electroplated board is bright and uniform without color difference, the surface area of ​​the blind hole is controlled at about 15 microns, and the depression is 0, which is consistent with the hole-filling effect produced by the iridium tantalum titanium mesh commonly used on the market, that is, the use of the above-mentioned carbon coated anode does not affect the effect of hole-filling electroplating.

[0037] The above conductive carbon coating anode is used in the hole filling copper plating process of the trivalent iron copper dissolving system, according to the following electroplating solution configuration, the electroplating solution is stirred by air, and the temperature is 25°C. The aperture of the blind hole on the test board is 125um and the layer is 70um. Electroplating parameters: current density: 1.6ASD, electroplating time 50min.

[0038] Copper sulfate pentahydrate: 250g / L;

[0039] Sulfuric acid: 35g / L;

[0040] Chloride ion: 60mg / L;

[0041] Total Fe: 3 g / L;

[0042] Ferric ion: 0.7 g / L;

[0043] Accelerator: 2mg / L;

[0044] Wetting agent: 0.8g / L;

[0045] Leveling agent: 0.5g / L.

[0046] The conductive carbon coating anode is used in the hole filling copper plating process of the copper dissolving system. The hole filling effect obtained according to the above parameters is as follows: Figure 2As shown, the surface of the electroplated board is bright and uniform without color difference, the surface area of ​​the blind hole is controlled at about 16 microns, and the depression is 0, which is consistent with the hole-filling effect produced by the iridium-tantalum-titanium mesh commonly used on the market. That is, the use of the above-mentioned carbon-coated anode in the trivalent iron hole-filling copper plating system will not affect the effect of the hole-filling electroplating.

[0047] Example 2

[0048] The preparation process of the conductive carbon coating anode of this embodiment is as follows:

[0049] 1) The titanium substrate is roughened. The roughening process includes placing the titanium substrate in a 8-12% hydrochloric acid solution, treating at 60° C. for 1 hour, washing with water and drying.

[0050] 2) Using high-purity carbon rod material as the target material, in a vacuum environment with a vacuum degree of 0.1 Pa, using 99.9% argon as the vacuum gas, controlling the vacuum coating temperature to 75 degrees, the coating time to 280 seconds, and the coating thickness to 8 microns, a dense graphite coating is applied on the treated titanium substrate by sputtering.

[0051] 3) The graphite-coated titanium anode is electrified in an airtight condition to heat it to 1500° C. for 8 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained.

[0052] The above conductive carbon coating anode is used in the direct current through-hole copper plating process, according to the following electroplating solution configuration, the electroplating solution stirring is air stirring + spraying, and the temperature is 25°C. The aperture of the through hole on the test board is 250um, the board thickness is 1500um, and the thickness-to-diameter ratio is 6:1. Electroplating parameters: current density: 2ASD, electroplating time 60min.

[0053] Copper sulfate pentahydrate: 75g / L;

[0054] Sulfuric acid: 230g / L;

[0055] Chloride ion: 60mg / L;

[0056] Accelerator: 1mg / L;

[0057] Wetting agent: 0.8g / L;

[0058] Leveling agent: 0.5g / L.

[0059] The conductive carbon coating anode is used in the through-hole copper plating process. The through-hole effect obtained according to the above parameters is as follows: Figure 3 As shown, the plated board surface is bright and uniform without color difference, and the through-hole deep plating capacity is above 75%, which is consistent with the through-hole electroplating effect produced by the iridium tantalum titanium mesh commonly used on the market, that is, the use of the above-mentioned carbon coated anode does not affect the through-hole electroplating effect.

[0060] The above conductive carbon coating anode is used in the pulse copper plating process, according to the following electroplating solution configuration, the electroplating solution stirring is air stirring + spraying, and the temperature is 25°C. The aperture of the through hole on the test board is 250um, the board thickness is 3000um, and the thickness-to-diameter ratio is 12:1. Electroplating parameters: current density: 2.5ASD, electroplating time 85min.

[0061] Copper sulfate pentahydrate: 75g / L;

[0062] Sulfuric acid: 230g / L;

[0063] Chloride ion: 60mg / L;

[0064] Accelerator: 1.5mg / L;

[0065] Wetting agent: 0.8g / L.

[0066] The conductive carbon coating anode is used in the pulse copper plating process. The through hole effect obtained according to the above parameters is as follows: Figure 4 As shown, the plated board surface is bright and uniform without color difference, and the through-hole deep plating capacity is above 110%, which is consistent with the pulse plating effect produced by the iridium tantalum titanium mesh commonly used on the market, that is, the use of the above-mentioned carbon coated anode does not affect the effect of pulse plating.

[0067] Uniformity comparison

[0068]

[0069] It can be seen from the above table that the coated anodes of Example 1 and Example 2 have better electroplating uniformity due to their good conductivity.

[0070] Comparative Example 1

[0071] The preparation process of the conductive carbon coating anode of this comparative example is as follows:

[0072] 1) The titanium substrate is roughened. The roughening process includes placing the titanium substrate in a 8-12% hydrochloric acid solution, treating at 60° C. for 1 hour, washing with water and drying.

[0073] 2) Use solvent acetone and adhesive methyl acrylate to evenly disperse graphite in the solution, evenly apply the dispersed graphite slurry on the roughened titanium substrate surface, put it in an oven, set it at 120 degrees, and bake it for 4 hours to remove excess solvent.

[0074] 3) The graphite-coated titanium anode is electrified in an airtight condition to heat it to 1000° C. for 5 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained.

[0075] The above conductive carbon coating anode is used in the hole filling copper plating process, according to the following electroplating solution configuration, the electroplating solution is stirred by air, the temperature is 25°C, the aperture of the blind hole on the test board is 125um, and the layer is 70um. Electroplating parameters: current density: 1.5ASD, electroplating time 50min.

[0076] Copper sulfate pentahydrate: 250g / L;

[0077] Sulfuric acid: 35g / L;

[0078] Chloride ion: 60mg / L;

[0079] Accelerator: 2mg / L;

[0080] Wetting agent: 0.8g / L;

[0081] Leveling agent: 0.5g / L.

[0082] The conductive carbon coating anode is used in the hole filling copper plating process. The hole filling effect obtained according to the above parameters is as follows: Figure 5 As shown, the blind hole surface is controlled at about 15 microns and the depression is 18 microns. The hole filling effect is far inferior to the hole filling effect brought by the anode of Example 1. This may be due to the way the slurry is applied and the poor conductivity of the coating leads to poor electroplating effect.

[0083] Comparative Example 2

[0084] The preparation process of the conductive carbon coating anode of this comparative example 2 is as follows:

[0085] 1) Using high-purity carbon rod material as the target material, in a vacuum environment with a vacuum degree of 0.1 Pa, using 99.9% argon as the vacuum gas, controlling the vacuum coating temperature to 75 degrees, the coating time to 280 seconds, and the coating thickness to 8 microns, a dense graphite coating is applied on the treated titanium substrate by sputtering.

[0086] 2) The graphite-coated titanium anode is electrified in an airtight condition to heat it to 1500° C. for 8 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained.

[0087] Compared with Example 2, Comparative Example 2 reduces the roughening process of the titanium substrate. Through the tape stripping experiment, it is found that the anode obtained by tape stripping Comparative Example 2 has more black carbon substances remaining on the tape, while the anode obtained by tape stripping Example 2 has less black carbon substances remaining on the tape. Figure 6 This indicates that roughening the titanium substrate (the roughening process is to place the titanium substrate in an 8-12% hydrochloric acid solution, treat it at 60°C for 1 hour, wash it with water and dry it) can enhance the bonding force between the titanium substrate and the coating carbon.

[0088] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.

Claims

1. A conductive carbon-coated anode for copper electroplating process, characterized in that: The titanium plate is used as the substrate, and a conductive carbon coating is applied on the surface by vacuum sputtering; The method for preparing a conductive carbon coating anode comprises the following steps: 1) Using high-purity carbon material as a target, a dense conductive carbon coating is applied on a titanium substrate by sputtering in a vacuum; 2) The carbon-coated titanium anode is electrified under air-tight conditions to heat it to 1000-1500° C. for 5-10 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained; The temperature of the vacuum coating carbon coating is 60-80° C., the coating time is 240 seconds to 300 seconds, and the coating thickness of the conductive carbon coating is controlled at 3-10 microns.

2. The conductive carbon coating anode for copper electroplating process according to claim 1, characterized in that: The conductive carbon coating is made of materials selected from carbon black, graphite, carbon nanotubes and graphene, and has a purity of more than 99.9%.

3. The method for preparing a conductive carbon coating anode for copper electroplating process according to claim 1 or 2, characterized in that: The steps include: 1) Using high-purity carbon material as a target, a dense conductive carbon coating is applied on a titanium substrate by sputtering in a vacuum; 2) The carbon-coated titanium anode is electrified in an airtight condition to heat it to 1000-1500° C. for 5-10 hours, and after cooling, a conductive carbon-coated anode for copper electroplating is obtained.

4. The method for preparing a conductive carbon coating anode for copper electroplating process according to claim 3, characterized in that: Before applying the carbon coating on the titanium substrate, the titanium substrate is also roughened.

5. The method for preparing a conductive carbon coating anode for copper electroplating process according to claim 4, characterized in that: The roughening process is to put the titanium substrate into 8-12% hydrochloric acid solution, treat it at 60° C. for 1 hour, wash it with water and dry it.

6. The method for preparing a conductive carbon coating anode for copper electroplating process according to claim 3, characterized in that: The vacuum condition is that the vacuum degree is lower than 1 Pa, and the vacuum gas is 99.9% argon.

7. The method for preparing a conductive carbon coating anode for copper electroplating process according to claim 3, characterized in that: The temperature of the vacuum coating carbon coating is 60-80°C, the coating time is 240 seconds to 300 seconds, and the coating thickness is controlled at 3-10 microns.

8. Use of the conductive carbon coating anode as claimed in claim 1 or 2 as an anode in a copper electroplating device for circuit boards.

Citation Information

Patent Citations

  • Low-cost surface treatment method for improving surface performance of titanium and titanium alloy for proton exchange membrane fuel cell polar plate

    CN114464818A

  • Composite anode plate for copper electroplating

    CN210104115U

Cited By

  • Protective adhesive tape for electroplating process and preparation method of protective adhesive tape

    CN120904802A